EVALUATION OF PHARMACEUTICAL CARE STANDARD IMPLEMENTATION BY PHARMACIST - Fatimah Nur Istiqomah; Satibi Satibi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The government has arranged regulations to establish the implementation of pharmaceutical care standard by pharmacists, such as Kepmenkes No. 1027/2004 about Standards of Pharmaceutical Care in Pharmacy. The government also issued a higher level of regulation, that is PP. 51/2009 about Pharmaceutical Practice. This study is aimed to observe the implementation for pharmaceutical care standard by pharmacist in Sleman Regency and determine the indicators of pharmacy services which have (not) been implemented by the pharmacist. Non experimental-quantitative and descriptive analysis were used in this study. The population were pharmacists practicing at the pharmacy in Sleman Regency. There were 35 pharmacists as sample, being determined by proportional random sampling. The data was collected by using questionnaire which was filled in by respondents, includes seven indicators of the implementation of pharmaceutical care based on PP No. 51/2009 and Kepmenkes No. 1027/2004. The data analysis was interpreted into categories, that are those with the percentage score of 81-100% as good category, 61-80% as adequate category and ≤ 60% as lacking category. The results showed the most optimum implemented indicator from the seven indicators according to the ranking, as follows indicator of workforce with the score of 95.24%, Supporting Factors of 91.10% and drug management of 81.90%. Those three indicators were categorized as good. While indicator of drug services with the score of 78.70%, administration of 77.62%, communication, information and education of 76.80% and evaluation of service quality 71.29%, were categorized as adequate. Among the 35 respondents, the results of the evaluation of standards implementation based on all indicators was 65.71% categorized as good category, 31.43% as adequate and only 2.86% as the lacking ones.Keywords : Implementation, Pharmaceutical Care, Pharmacy, Sleman